Tinjauan Yuridis dalam Penyelesaian Polemik Penerbitan Obligasi Daerah di Indonesia - M. Rasyid Ridho (JIMLY LEGAL YUSTISIA JOURNAL, 2023)
On the one hand, bonds for investors are a long-term investment, but on the other hand, for the government as the bond issuer, it is a debt that must be repaid. The obligation to pay debts creates uncertainty for investors if they pay attention to the provisions of Article 49 Paragraph (4) of Law Number 1 of 2004 concerning the State Treasury which regulates that state/regional property is prohibited from being handed over to other parties. parties as payment of bills to the central government /area. The purpose of this paper is to analyze the formation and settlement of regional bond polemics in Indonesia. This paper uses a type of normative research, using statutory and conceptual approaches. The research results show that bond protection for regional governments in Indonesia is contained in general laws and special regulations. Investors who purchase Municipal Bonds are protected by the Consumer Protection Law, Financial Services Authority (OJK) Regulations, and other related regulations. Regional Bonds that fail to pay can be resolved through litigation and non-litigation. Non-litigation resolution through Alternative Dispute Resolution (APS) must be prioritized.